PERBANDINGAN PENGGUNAAN LOCAL-NAME BRAND DAN FOREIGN-NAME BRAND PADA PRODUK FASHION DI KOTA MALANG - Novita Putri Diantanti; Sunaryo Sunaryo; Mintarti Rahayu (Jurnal Bisnis dan Manajemen, 2018)
The purpose of this study are to know the distinction of brand attitude, purchase intention, and consumer knowledge in fashion product which using local-name brand and foreign-name brand, also the influence of brand attitude toward purchase intention with moderate effect of consumer knowledge. Population including students in University of Brawijaya Malang. Total samples are 260 respondents divided into two groups, local-name brand and foreign-name brand group. Data analysis technique used is t-Test and PLS analysis. This study found that there is difference consumer knowledge in local-name brand and foreign-name brand group. But there are no significant differences brand attitude and purchase intention in both groups. Results of this study indicates that there are significant and positive influence in the relationship between brand attitude toward purchase intention. Objective knowledge moderated relationship between brand attitude toward purchase intention in local-name group only. Besides, those relationship is not moderated by subjective knowledge in both groups. Therefore, company can use a brand name that characterizes the origin of the product, especially when the product is a local product. DOI : https://doi.org/10.26905/jbm.v5i1.2319